2004
DOI: 10.1002/cyto.a.20026
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein–propidium iodide (GFP‐PI) based assay for flow cytometric measurement of bacterial viability

Abstract: Background Several staining protocols have been developed for flow cytometric analysis of bacterial viability. One promising method is dual staining with the LIVE/DEAD BacLight bacterial viability kit. In this procedure, cells are treated with two different DNA‐binding dyes (SYTO9 and PI), and viability is estimated according to the proportion of bound stain. SYTO9 diffuses through the intact cell membrane and binds cellular DNA, while PI binds DNA of damaged cells only. This dual‐staining method allows effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 24 publications
2
93
0
Order By: Relevance
“…Previous studies that used FCM analysis of SYTO/PI labeled bacteria showed that not only intact (SYTO 9 positive) and damaged cells (PI positive) are observed, but that double-stained cells (SYTO 9/PI) are also detected [26][27][28][29]. For results, SYTO 9 positive cells were referred to as "live", PI positive cells as "dead", and cells displaying a double positive signal (SYTO 9/PI) were designated "injured".…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Previous studies that used FCM analysis of SYTO/PI labeled bacteria showed that not only intact (SYTO 9 positive) and damaged cells (PI positive) are observed, but that double-stained cells (SYTO 9/PI) are also detected [26][27][28][29]. For results, SYTO 9 positive cells were referred to as "live", PI positive cells as "dead", and cells displaying a double positive signal (SYTO 9/PI) were designated "injured".…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…However, since bacterial surface colonization starts with the adhesion of individual bacteria, the presented assay provides a versatile new tool for high spatial and temporal evaluation of bacterial viability on engineered surface coatings. The assay thus adds to the previously reported eGFP/PI flow cytometry assay that was limited to viability determination of suspended bacteria [21] and to the eGFP/PI endpoint viability study of groundwater E. coli [34].…”
Section: Discussionmentioning
confidence: 99%
“…We compared the performance of our eGFP/PI assay to the well-established SYTO ® 9/PI endpoint dual staining assay and found identical detection efficiencies of dead E. coli (Additional file 1: Figure S2). The SYTO ® 9/PI assay itself has been extensively compared to the above-mentioned viability tests [17,19,21,26,36] and showed comparative results to the solution based CFU assay as well as to other microscopy based endpoint viability protocols including the CTC assay. The added advantage of our assay is the ability to monitor the viability of adherent bacteria in real-time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI stains dead bacteria in which cell membranes are destroyed. We were able to distinguish viable bacterial cells from the dead cells using these reagents 24,25 . Both reagents work within minutes, and we were able to determine penetration of these dyes in bacterial cells in a solution containing MEE.…”
Section: Bactericidal Activity With Aementioning
confidence: 99%